2015
DOI: 10.7860/jcdr/2015/10644.5498
|View full text |Cite
|
Sign up to set email alerts
|

Extradural Spinal Metastasis of Adenoid Cystic Carcinoma (ACC): A Case Report

Abstract: A 45-year-old male presented to the neurosurgery out patient department with diffuse low back pain radiating to the right girdle since two months and inability to walk since two days. The pain was continuous in nature, exaggerated on activity and was persistent during the night with relief on taking analgesics. He had no associated co-morbid illness and or habituations. There was no history of trauma or tuberculosis.Patient gave a past history of primary submandibular gland tumour resection 11 years back follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The liver was reported in several studies as a single site of the systemic spread of the disease. Organs with less common metastasis include the breast and larynx, and those which are rarely involved in SACC metastasis include the pituitary gland, the sternum, the dorsal spine [ 31 ], the choroid, the toe bones, and the pericardium [ 31 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The liver was reported in several studies as a single site of the systemic spread of the disease. Organs with less common metastasis include the breast and larynx, and those which are rarely involved in SACC metastasis include the pituitary gland, the sternum, the dorsal spine [ 31 ], the choroid, the toe bones, and the pericardium [ 31 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have also reported the liver as a primary site for systemic disease spread. While metastasis to the breast and larynx is less frequent, extremely rare instances of metastasis have been noted in areas such as the pituitary gland, sternum, dorsal spine [ 80 ], choroid, bones of the toe, and the pericardium [ 80 , 81 , 82 , 83 , 84 , 85 , 86 ]. Recurrences in ACC are frequent, and in post-initial treatment, the chances of reoccurrence can be up to 50% in particular cases [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 10 , 11 A limited number of spine metastasis cases of ADCC from other gland origins of head and neck, such as parotid gland, submandibular gland, tongue base, and lacrimal gland have been reported. 12 - 14 However, spinal metastatic ADCC arising from ceruminous gland in the EAC is exceedingly rare. Marchesini et al 15 reported a male patient complaining of back pain and worsening myelopathy and was diagnosed with intramedullary spinal cord metastasis from ADCC of EAC.…”
Section: Discussionmentioning
confidence: 99%